Thick escaping magnetospheric ion layer in magnetopause reconnection with MMS observations - T. Nagai; N. Kitamura; H. Hasegawa; I. Shinohara; S. Yokota; Y. Saito; R. Nakamura; B. L. Giles; C. Pollock; T. E. Moore; J. C. Dorelli; D. J. Gershman; et al. (Geophysical Research Letters)
Abstract The structure of asymmetric magnetopause reconnection is explored with multiple point and high‐time‐resolution ion velocity distribution observations from the Magnetospheric Multiscale mission. On 9 September 2015, reconnection took place at the magnetopause, which separated the magnetosheath and the magnetosphere with a density ratio of 25:2. The magnetic field intensity was rather constant, even higher in the asymptotic magnetosheath. The reconnected field line region had a width of approximately 540 km. In this region, streaming and gyrating ions are discriminated. The large extension of the reconnected field line region toward the magnetosheath can be identified where a thick layer of escaping magnetospheric ions was formed. The scale of the magnetosheath side of the reconnected field line region relative to the scale of its magnetospheric side was 4.5:1.